FULFILMENT OF DISABILITY RIGHTS IN TOURISM POLICY - Pravita, Vina Dini; Sembada, Andhika Djalu; Muharam, Ricky Santoso; Prasetyo, Danang (Kepariwisataan: Jurnal Ilmiah, 2023)
AbstractThe fulfillment of various disability rights, especially in the tourism policy sector, needs serious attention. The existence of regulations on disability rights regarding tourism has been regulated in the regulation of  Law Number 8 of 2016 article 16 of cultural and tourism rights as a guideline for fulfilling the rights of persons with disabilities, especially in the tourism sector. This research method uses qualitative research with literature reviews from various sources which are then described in descriptive analysis. Data processing from various problems or cases of persons with disabilities in the tourism sector related to the protection of disability rights in tourism with primary and secondary data. The results of the study found that there is still a need for seriousness for the government in implementing tourism policies that are friendly to people with disabilities following the dimensions of access and examples of Inclusive Practices in tourism such as building needs and road access, transportation, access to information and communication needed for people with disabilities as the fulfillment of disability rights following the agreement of various countries in the form of the Convention on the Rights of Persons with Disabilities (CRPD). AbstrakPemenuhan berbagai hak disabilitas khususnya di bidang kebijakan pariwisata perlu mendapat perhatian serius. Keberadaan pengaturan hak disabilitas terkait kepariwisataan telah diatur dalam peraturan Undang-Undang Nomor 8 Tahun 2016 pasal 16 tentang hak budaya dan kepariwisataan sebagai pedoman pemenuhan hak penyandang disabilitas khususnya di bidang pariwisata. Metode penelitian ini menggunakan penelitian kualitatif dengan kajian literatur dari berbagai sumber yang kemudian dideskripsikan secara deskriptif analisis. Pengolahan data dari berbagai permasalahan atau kasus penyandang disabilitas di bidang pariwisata terkait perlindungan hak disabilitas di bidang pariwisata dengan data primer dan data sekunder. Hasil kajian menemukan bahwa masih diperlukan keseriusan pemerintah dalam mengimplementasikan kebijakan pariwisata yang ramah penyandang disabilitas sesuai dengan dimensi akses dan contoh Praktek Inklusif dalam pariwisata seperti kebutuhan bangunan dan akses jalan, transportasi, akses informasi dan komunikasi yang dibutuhkan penyandang disabilitas sebagai pemenuhan hak disabilitas sesuai dengan kesepakatan berbagai negara dalam bentuk Konvensi Hak Penyandang Disabilitas (CRPD).